Biokonversi Sampah Organik Pasar Menjadi Biogas Menggunakan Starter Effective Microorganisms (EM4) - I Gusti Made Sanjaya (Sains dan Matematika, 2012)
Bioconversion of organic waste into biogas has been studied using a variation of effective micro-organisms starter, EM4. Optimum bioconversion resulted in the addition of EM4 9% to produce biogas as much as 328.17 ml. Biogas at optimum bioconversion conditions had the composition of methane gas 61.97% and 36.04% carbon dioxide.